New Details from the History of Georgian Emigration - Avtandil Nikoleishvili, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
The main field of activity of a large portion of Georgian emigrants who left the country in order to escape from the dictatorial regime of the Soviet Union was a political, cultural, public, and creative arena. Unfortunately, because of the limited access to many important documents related to the history of Georgian emigration, the history of emigration has not been studied adequately, and a lot remains to be discovered. To fill this gap, we present the life story and works of Lado Arveladze, an almost unknown emigrant, Georgian writer and public figure. Unfortunately, the works and heritage of this talented fiction writer and ardent patriot are unknown not only to the general public, but also to specialists.